The Problem of The Application of The Doctrine of Inclusion In The Eradication of Terrorism In Indonesia - Hakim, Lukman (SASI, 2023)
Introduction: The criminal act of terrorism which is the common enemy of many countries in the world including Indonesia which in fact is carried out by more than one perpetrator even further than that which is terrorized in a particular terrorist organization, so that the teaching of inclusion in criminal law becomes important to be applied appropriately.Purposes of the Research: This paper aims to determine whether it is appropriate to use the articles contained in the law on combating terrorism related to the doctrine of inclusion of perpetrators of criminal acts of terrorism that are generally committed by more than one person in a particular terrorist organization.Methods of the Research: The type of research is normative juridical with analysis using legal documents in the form of primary legal materials, secondary legal materials, and tertiary legal materials.Results of the Research: In the field of practice, the application of the doctrine of inclusion in the provisions of the law on Combating Terrorism is often cause legal problems, especially in the context of determining the criminal liability of the perpetrators of terrorism, this has resulted in difficulties for law enforcers, especially public prosecutors and judges to determine criminal liability for each perpetrator, in contrast to the application of, so that the punishment for the perpetrators can be more effective and meet the sense of justice and legal certainty.